(untitled) (Global Journal of Human-Social Science, 2011)
Most studies have found that at the contextual level e g degree programme approach to study is stable over time e g Busato Prins Elshout and Hamaker 1998 At the situational level e g a module the results are possibly less equivocal with studies reporting a decrease in deep approach at the end of the module e g Newstead 1998 Fazey Lawson 2000 conducted a study that was contingent upon the use of a teaching approach that consistently raises expectations that a deep approach to learning is required and uses an assessment methodology that will reward such an approach They found that students taught using this constructively aligned methodology maintained their deep approach to study and significantly decreased their surface approach at the assessment period of the module In a follow up study Lawson Fazey and Fazey 2006 further explored this concept in a variety of subjects finding that modules classified as being strongly aligned and fostering deep approaches to learning had students who scored significantly higher on deeper approaches to learning and intrinsic motivation than those in modules with low alignment that fostered a surface approach This present study looks at changes over time in students approaches to learning and motivational orientation The results show changes over time in these student factors related to teaching approach and alignment